Disorders of Magnesium Metabolism: Hypomagnesemia and Hypermagnesemia - Tinawi, Mohammad (Archives of Clinical and Biomedical Research, 2020)
Magnesium (Mg) is the second most abundant intracellular cation. It is a major factor in numerous cellular functions. Mg is a cofactor in hundreds of enzymatic reactions. Mg is essential for cellular energy production because it is a cofactor for adenosine triphosphate (ATP). Mg metabolism is linked to potassium (K) and calcium (Ca) metabolism. Hypomagnesemia is associated with several chronic diseases such as insulin resistance, hypertension (HTN) and osteoporosis. Severe hypermagnesemia is associated with significant toxicity. Mg can be easily replaced orally (PO) or intravenously (IV). Disorders of Mg metabolism are overlooked at times because Mg is not included in routine chemistry panels.